Strategi Promosi melalui Media Sosial dalam Meningkatkan Penjualan pada Usaha Kedai Om Bew & Billiard - Fazreen, Syahira; Billah, Faiq; Aziizah, Yaafi'ah; Faruqi, Faris; Hendryadi, Hendryadi (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
This community engagement program aims to enhance exposure and increase sales for a microenterprise by implementing a social media-based digital marketing strategy. The partner for this program is Kedai Om Bew & Billiard, targeting Generation Z with moderate income, active on social media, and having a high social lifestyle. The method used is an action research approach through intensive mentoring in creating regular marketing content on Instagram and TikTok platforms. The results show a significant improvement in digital reach, with 631 profile visits and 39,227 views on TikTok, 2,565 profile visits and 68,183 views on Instagram. The evaluation was conducted through engagement analysis and visitor surveys, revealing increased customer interest and interaction. Implementing this digital marketing strategy contributed to a 52.54% increase in sales compared to the previous quarter. These findings demonstrate that promotional digitalization through social media is an effective solution to support the growth of MSMEs in the digital era.